UMP student attendance system by using QR code (USA-QC) - Nurul Fazreen Elia, Zanudin (2019)
Currently, UMP using the IMS system to take the student attendance which it requires the lecturers to key in the attendance every day. But unfortunately, that IMS system have their own limitations which make the system inefficient to use. Basically, that system requires Java as their platform to run the system. So another problem will arise if the lecturer’s laptop does not support the platform of Java. In order to overcome this issue, UMP Student Attendance System by Using QR Code (USA-QC) is developed. USA-QC enables the student to submit their attendance by scanning the QR Code during the class as well as it will ease the lecturers to manage their student attendance list. In order to develop the system, it required to use the Microsoft Visual Studio 2010 to develop the attendance system and use Android Studio to develop the android mobile application for the UMP students. In general, the scope for this project is more to lecturer and students. This improvement of attendance system is just by scanning the QR Code in order for the students to submit their attendance to the class. The QR Code will be displayed by the lecturers during the class. The development of the project applied to this system is Rapid Application Development (RAD) which this method is split into four phases. Lastly, by applying this system hopefully can improve the management of student attendance system at UMP.